Service-oriented architecture : an integration blueprint : a real-world SOA strategy for the integration of heterogeneous Enterprise systems : successfully implement your own enterprise integration architecture using the Trivadis Integration Architecture Blueprint /: an integration blueprint : a real-world SOA strategy for the integration of heterogeneous Enterprise systems : successfully implement your own enterprise integration architecture using the Trivadis Integration Architecture Blueprint. (2010) - Unknown
No abstract available